2004
DOI: 10.1300/j013v40n02_01
|View full text |Cite
|
Sign up to set email alerts
|

Weight and Behavioral and Psychosocial Factors Among Ethnically Diverse, Low-Income Women After Childbirth: I. Methods and Context

Abstract: Low-income ethnic minority women have a higher vulnerability to postpartum weight gains or plateaus. High depressive symptoms occurred in all ethnic groups examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Pre-pregnancy weight and GWG were self-reported by mothers and may not have been accurate. However, self-reported weight in similar contexts has shown to be reliable estimates of weight [52, 53]. Self-report of GWG within the first year postpartum has also shown to be a reliable measure as compared to birth certificate data [54].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Pre-pregnancy weight and GWG were self-reported by mothers and may not have been accurate. However, self-reported weight in similar contexts has shown to be reliable estimates of weight [52, 53]. Self-report of GWG within the first year postpartum has also shown to be a reliable measure as compared to birth certificate data [54].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The relatively small number of mothers also limited statistical power, so that some important but more modest associations may not have been detected as statistically significant. Mother's pregnancy weight gain was self-reported as in other studies (Walker et al, 2004;Boury, Larkin, & Krummel, 2004). However, mothers' reports of routine prenatal care and the emphasis on weight gain during pregnancy make it a reasonable assumption that women had access to, and could track and accurately report this information.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive studies and studies with low-income postpartum women have been reported in the literature. 5,6 There are few intervention studies, although one study reported increased physical activity after a psychosocial intervention. 7 The purpose of the present intervention study was to decrease environmental barriers to promote physical activity in low-income women.…”
mentioning
confidence: 99%